A Highly Selective and Sensitive Fluorescent Sensor for Copper(II) Ion Characterized by One Dichlorofluorescein Moiety and Two Azathia-Crown Ether - Jiang, Yuzhu; Huang, Zhong; Dai, Huajun; Wang, Lihua; Ying, Liu; Kou, Xingming (Asian Journal of Chemistry, 2013)
A new fluorescent sensor 1, which functionalized with one dichlorofluorescein moiety as fluorogenic signaling subunit and two azathia-crown ether macrocyclic as binding site was designed, synthesized and characterized. It was found that sensor 1 can selectively recognize Cu2+ by a remarkable emission quenching in DMSO-H2O (1:1, v/v), which was attributed to the 1:2 complex formation between 1 and Cu2+, while other ion including K+, Na+, Mg2+, Zn2+, Ba2+, Co2+, Ca2+, Fe2+, Fe3+, Pb2+, Pb2+, Ni2+ and Ag+ induced no or much small fluorescence changes. In addition, the sensor 1 exihibited a rapid, stable and linear response to Cu2+ in the concentration range from 5 × 10-7 to 1 × 10-5 mol L-1 with a detection limit as low as 8.7 × 10-8 mol L-1. Furthermore, the sensor 1 was applied to practical determination of Cu2+ in different water samples with satisfactory results.